Della Walker (Mrs. Clinton Walker) residence, exterior gate art (1950)
Gate art outside the house originally designed by Frank Lloyd Wright. Presents a bowl full of clear blue balls atop a pedestal residing next to an exterior gate. The Pacific Ocean lies in the background along with the waning of the California coast.